Dad and the dinosaur - Choldenko, Gennifer, 1957- (G.P. Putnam's Sons, 2017)
"A boy keeps a toy dinosaur in his pocket to help him be brave like his dad--but when the dinosaur goes missing, Dad knows just what to do"--